Clinical Correlation of Adenoviral Load in the Respiratory Tract Measured by Digital PCR in Immunocompromised Children. (23rd January 2023) - Hijano, Diego R; Ferrolino, Jose A; Hidinger, Jennifer; Brazelton, Jessica N; Gu, Zhengming; Suganda, Sri; Glasgow, Heather L; Allison, Kim J; Peterson, Megan; Dallas, Ronald H; Maron, Gabriela; Hayden, Randall T
Abstract: Immunocompromised patients can have life-threatening adenoviral infection. Viral load in blood and stool is commonly used to guide antiviral therapy. We developed and evaluated a digital polymerase chain reaction assay to quantify human adenovirus in the respiratory tract and showed that higher peak load correlates with disseminated infection, mechanical ventilation, and death.